Investing in a Research Revolution for LGBTI Inclusion - World Bank; UNDP (World Bank, Washington, DC, 2016)
Lesbian, gay, bisexual, transgender, and intersex (LGBTI) people throughout the world have led global efforts to raise awareness of their experience of ongoing discrimination, exclusion, and violence. Despite some gains that have made information more available, huge gaps in research and data on LGBTI experiences persist in every country, blocking progress toward inclusion and the realization of human rights for all. Clearly, significant donor investment in strategic research on LGBTI inclusion is needed, to provide a reliable evidence base that can inform policies, legislation, programs, and investments to advance the human rights and inclusion of LGBTI people in national and global efforts. This paper highlights for discussion the critical research and knowledge gaps with regard to human rights and inclusion for LGBTI people that require investments to ensure that they are part of the human rights and development agendas. In light of these significant gaps, the paper outlines a number of high-priority research needs that have been identified as a result of wide-ranging consultations with civil society organizations, governments, research institutions, human rights and development agencies, and researchers. Finally, the paper presents a set of proposed strategic investments to focus on those high-priority topics. These investments would also build an LGBTI research infrastructure to produce and share knowledge about LGBTI people and issues.